Life cycle changes and career development: an exploration of influences on career change decisions - Sumner, Lesley (Cranfield University, 1993)
The purpose of this research was to identify factors which influence decisions concerning significant career moves among older workers and women returners. A questionnaire survey of older workers was conducted in order to elicit the salient attitudes to, experience of, and satisfaction with work of job changers and non-changers aged 50 years and over, employed within a nationwide retail organisation. Results were based on 228 questionnaires. Respondents ranged in age from 50 to 73 years, 54% were female, 46% male. Respondents demonstrated a significant increase in self-perception the perceived benefits of working far outweighed perceived difficulties. There were differences between men and women in the prompts to change employment and in salient attitudes to work. A questionnaire survey of women returners was conducted to explore items women considered when embarking on college courses, their experience of these same items while at college, and the relationship between the decision considerations and subjective well-being. The results of 336 questionnaires were analysed. Respondents ranged in age from 16 to 62 years. The expected benefits of attending college were given greater consideration than expected risks, confirming work by Janis and Mann (1977). Actual benefits and actual problems were overall the most useful predictors of college related well-being. There were differences between young and mature students, women with and without partners, and those with and without dependents in terms of items on the motivator for college attendance, expected benefit and risk and actual benefit and problem scales. The Warr Subjective Well Being (SWB) scale was shown to be a reliable measure of college related well-being. The wide age range and life experience of respondents in both studies confirms the utility of life event models of development and the desirability of developing a flexible person-centred counselling model for decision making.